Movement analysis 3D Character Animation Assisted On Kinect XBOX One Devices - Charles De Haan (Jurnal Mantik, 2022)
The technology of Motion Capture is used to produce motion animation by capturing the movement of the artist, then recorded and applied on virtual 3D. This is especially helpful in animation movements that are difficult to work with conventionally, as imitating human body movements realistically is quite difficult for some animators. The use of Kinect Xbox One to overcome various human limitations in creating animated movements on virtual 3D objects in the form of humans or animals. The purpose of this study is to describe how to use the Kinect Xbox One and explore its ability to detect basic human movements that can be used by animators to be applied to virtual 3D objects. The results of this study indicate that the use of Kinect Xbox One as a Motion Capture is good enough to be used to produce animated movements, especially basic human movements in the type of basic locomotor movements, namely walking, running, jumping and jumping, basic movements of balance skills, namely bending, stretching, twisting and swing and basic manipulative movements, namely throwing, punting and kicking.